Central Inhibition of Tumor Necrosis Factor Alpha Reduces Hypertension by Attenuating Oxidative Stress in the Rostral Ventrolateral Medulla in Renovascular Hypertensive Rats - Carvalho-Galvão, Alynne; Guimarães, Drielle D.; De Brito Alves, José L.; Braga, Valdir A. (Frontiers in Physiology, 2019)
Inflammation in the central nervous system is being considered a key player linked to neurogenic hypertension. Using combined in vivo and in vitro approaches, we investigated the effects of central inhibition of TNF-α on blood pressure, sympathetic tone, baroreflex sensitivity and oxidative stress in the rostral ventrolateral medulla (RVLM) of rats with 2-kidney-1-clip (2K1C) renovascular hypertension. Continuous infusion of pentoxifylline, a TNF-α inhibitor, into the lateral ventricle of the brain for 14 days reduced blood pressure and improved baroreflex sensitivity in renovascular hypertensive rats. Furthermore, central TNF-α inhibition reduced sympathetic nerve activity and blunted the increased superoxide accumulation in the RVLM of 2K1C rats. Our findings suggest that TNF-α play an important role in the maintenance of sympathetic vasomotor tone and increased oxidative stress in the RVLM during renovascular hypertension.